Exercise in a hot environment: comparison of two different fluid intake patterns - Ferguson, M. A.; Mccoy, S.; Mosher, P. E. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: Extensive research has been undertaken in the area of exercise and hydration. Most work has focused on prehydration. Less is known about different fluid intake patterns during exercise and its effect in thermoregulatory variables in hot environments. This study attempted to determine if ingesting fluid either in a single bolus or intermittently during exercise had different results in thermoregulatory parameters and thirst in a hot environment. Methods: Six moderately trained men and women (n=6, 5 male, 1 female; mean±SD: age 28.5±2.5 y; weight 74.4±3.3 kg, V.O2max 45.9±3.7 ml.kg.min-1) completed 2 exercise sessions in a randomized, counterbalanced order. Treatment 1 (bolus) consisted of 60 minutes of bicycling at 50% of V.O2max in a climatic chamber (dry bulb temperature, 35°C, 45% relative humidity). Subjects consumed 1 000 ml of plain cool (22°C) water immediately before exercise. During treatment 2 (intermittent) the same environmental conditions were present, but subjects consumed 250 ml of water immediately before exercise. During the bicycle ride, subjects consumed 250 ml of cool water at minutes 15, 30, and 45 of exercise for a total trial volume of 1 000 ml. Tympanic ear temperatures, heart rates, rating of perceived exertion (RPE), and thirst scale data were collected immediately before exercise and at minutes 10, 20, 30, 40, 50, and 60 of exercise. Results: No statistical differences were noted in temperature between treatments (P>0.05). Lower heart rates and thirst scores were noted for the bolus treatment at various time points (P<0.05). Little differences were noted between treatments for RPE during exercise. Conclusion: These results suggest that consumption of water in a single bolus is more beneficial for some aspects of thermoregulatory control and delaying thirst during exercise in the heat. Additional mechanistic studies with larger sample sizes are warranted.